2015
DOI: 10.1007/s40279-015-0324-9
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Repeated-Sprint Training on Field-Based Fitness Measures: A Meta-Analysis of Controlled and Non-Controlled Trials

Abstract: Repeated-sprint training can induce small to large improvements in power, speed, repeated-sprint ability and endurance, and may have relevance for training in team sports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
103
2
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(125 citation statements)
references
References 61 publications
(72 reference statements)
5
103
2
7
Order By: Relevance
“…The results of the present study also showed a significant improvement in power performance following COD and RS training. These results were also in accordance with previous studies [3436]. Indeed, Jovanovic et al [34] indicated that 8 weeks of a specific COD training programme appears to be an effective way of improving power performance in young soccer players.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of the present study also showed a significant improvement in power performance following COD and RS training. These results were also in accordance with previous studies [3436]. Indeed, Jovanovic et al [34] indicated that 8 weeks of a specific COD training programme appears to be an effective way of improving power performance in young soccer players.…”
Section: Discussionsupporting
confidence: 92%
“…However, there was no significant difference between groups in the 10 to 30 m straight sprint performance. The result of the present study was also in line with scientific literature [36]. Indeed, it has been indicated that RS training allowed improvement in maximal speed (30 m) among young elite soccer players.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Coaches working with teams of players across maturation groups may need to be creative in the way they deliver metabolic conditioning to produce positive adaptations throughout. Repeated sprint training methods could provide an adaptable tool for coaches within this age group given the short and sharp nature of the stimulus and potential benefits on neuromuscular and metabolic fitness (52).…”
Section: Table 3 Herementioning
confidence: 99%
“…The application of various modes of HIIT in the development of fitness in team sport players has been investigated (Buchheit & Laursen, 2013;Taylor, Macpherson, Spears, & Weston, 2015;Weston, Taylor, Batterham, & Hopkins, 2014). The majority of studies have focused on the inclusion of one mode of HIIT in an overall training program as either additional, or replacement training.…”
Section: Introductionmentioning
confidence: 99%